Digital fabrication in the process of creation of the parametric concrete fencings - Marcin Giedrowicz (Budownictwo i Architektura, 2020)
This paper is a summary of the research on parametric design methods and digital fabrication in architecture and industrial design. Through the author’s projects, he presents how effective parametric designing process can be in contemporary architecture. This publication is a testimony of a long and full production process of a set of concrete fencings – from design part, through prototyping, digital fabrication, post-production, concreate fabrication and selling process. The design part of this research pertains to algorithmic design methods in Grasshopper software as well as presents a broad range of various technological aspects involved in the fabrication process.  In the conclusion part of this paper, the author discloses his expectations towards the future of concrete fencing in Poland and describes a set of appropriate rules that foster a further development of this technology.